Tidal energy resource characterization and assessment in Turnagain Arm of Cook Inlet: from pilot to commercial scales (Proceedings of the European Wave and Tidal Energy Conference, 2025)
There have been significant efforts worldwide in the development of tidal stream energy as a potential renewable energy source to mitigate the climate crisis.  Cook Inlet in the State in Alaska, USA, is one of the top energetic tidal sites in the world, with great potential for tidal energy exploitation. Cook Inlet consists of several strong tidal current hotspots in the USA, including East and West Forelands, Turnagain Arm and Knik Arm. Currently, most of the tidal stream resource assessment studies have focused on the Foreland areas, where the strongest tidal currents are present in Cook Inlet. However, the tidal energy resource in Turnagain Arm in the upper Cook Inlet has never been characterized in detail. Micro-grid scale tidal energy development could play an important role in helping remote communities in Alaska to meet the power needs.  In this study, we developed a high-resolution three-dimensional tidal hydrodynamic model using the Finite Volume Community Ocean Model to simulate the tidal currents and characterize tidal energy resource in Turnagain Arm. The model was validated with field data for water levels and tidal currents. Model performance was evaluated using error statistics, including root-mean-square-error, scatter index, bias, and linear correlation coefficient. Model configuration, validation, and resource characterization follow closely the International Electrotechnical Commission Technical Specification for tidal energy assessment and characterization. Specifically, a set of tidal energy variables, including tidal power density, probability of velocity exceedance, and annual energy production were used to characterize the energy potential. Extractable energy was assessed using a tidal energy conversion module in the numerical model based on various specific tidal turbine technologies and different array layouts, with turbine farm sizes ranging from pilot scale to commercial scale in Turnagain Arm. Extractable power per turbine was calculated and analyzed to identify the optimal siting location for turbine farm. Finally, far-field effects of tidal energy extraction on tidal circulation and its implication for sediment erosion near the tidal turbine farms are analyzed by comparison of flow fields with and without tidal turbine farms. This study demonstrates that Turnagain Arm has a great potential for tidal energy harvesting at both pilot and commercial scales, which could be integrated into the nearby power grid system to supplement the power demand of the Railbelt of Alaska region, which covers about 75% of the population of Alaska.